(untitled) (Journal of Applied Oral Science, 2014)
Objective: To evaluate the impact of the type of root canal preparation, intraradicular post and mechanical cycling on the fracture strength of roots. Material and Methods: eighty human single rooted teeth were divided into 8 groups according to the instruments used for root canal preparation (manual or rotary instruments), the type of intraradicular post (fiber posts- FRC and cast post and core- CPC) and the use of mechanical cycling (MC) as follows: Manual and FRC; Manual, FRC and MC; Manual and CPC; Manual, CPC and MC; Rotary and FRC; Rotary, FRC and MC; Rotary and CPC; Rotary, CPC and MC. The filling was performed by lateral compactation. All root canals were prepared for a post with a 10 mm length, using the custom #2 bur of the glass fiber post system. For mechanical cycling, the protocol was applied as follows: an angle of incidence of 45°, 37°C, 88 N, 4 Hz, 2 million pulses. All groups were submitted to fracture strength test in a 45° device with 1 mm/ min cross-head speed until failure occurred. Results: The 3-way ANOVA showed that the root canal preparation strategy (p